Assessing infection related to short-term central venous catheters in the perioperative setting - Ángel Becerra-Bolaños; Yurena Domínguez-Díaz; Héctor Trujillo-Morales; Sergio Cabrera-Doreste; Oto Padrón-Ruiz; Lucía Valencia-Sola; Nazario Ojeda-Betancor; Aurelio Rodríguez-Pérez (Scientific Reports)
Abstract Central venous catheter (CVC) cannulation can be accompanied by serious complications. The appearance of catheter-related infections is associated with high morbimortality. The aim of this study is to evaluate the incidences of colonization and central line-associated bloodstream infections (CLABSI) in short-term CVCs in the elective surgery setting, as well as to analyze the related risk factors. Prospective observational study including patients undergoing elective surgery with a CVC inserted perioperatively. Patients with current infection, taking preoperative antibiotics, those planning to have CVC for longer than 14 days, those under 18 years old, and those refusing to participate were excluded. Patients without cultures at the moment of CVC retrieval were not included. 200 patients were included, with a mean catheter duration of 6.8 ± 3.1 days, and a total duration of 1,358 days. Incidence of colonized catheters was 6% (8.84/1000 catheter-days), and 3.5% had CLABSI (5.15/1000 catheter-days). Catheter duration was longer in patients whose CVCs had been removed due to suspected infection (p < 0.0001). The risk factors for catheter colonization were a history of oncological disease (p = 0.022), ischemic heart disease (p = 0.019), as well as jugular venous catheterization (p = 0.019). No relationship was detected between colonization and operator experience (p = 0.050), ultrasound-guided cannulation (p = 0.565), or number of attempts (p = 0.379). The risk factors for CLABSI were: age over 60 years (p = 0.041) and oncological disease (p = 0.021). CLABSI was neither related to operator experience (p = 0.178), ultrasound-guided cannulation (p = 0.373), or number of attempts (p = 0.379). Although CVCs were in place for a short time and in a controlled setting, we observed high incidences of colonization and CLABSI. The risk of catheter colonization depends on other factors rather than catheter duration.